Autoantigens are translocated into small apoptotic bodies during early stages of apoptosis - Schiller, Martin; Bekeredjian-Ding, Isabelle; Blank, Norbert; Ho, Anthony Dick; Lorenz, Hanns-Martin (Cell death and differentiation, 2008)
A dysregulation of apoptosis or an ineffective clearance of apoptotic material is suspected to be involved in the pathogenesis of systemic lupus erythematodes. Subcellular fragments such as apoptotic bodies (ABs) have been recognized as modulators of intercellular communication and immune function. In this context, we have been interested whether nuclear and cytoplasmic antigens are relocated into ABs. In the present study, we characterized ABs isolated from apoptozing lymphoblasts. We found an accumulation of the linker-histone (histone 1) as well as the core-histones (histone 2A, histone 2B, histone 3, histone 4) in ABs. Further, they contained DNA, RNA and the ribonuclear protein La/SSB. Proteins such as cytochrome c, HSP 70, prohibitin, p53, nuclear matrix antigen or lamin B were excluded from ABs. The content of ABs differed from that observed in membrane microparticles isolated from viable cells. Formation of ABs occurred early during apoptosis. It was observed before DNA-degradation or phosphatidylserine exposure was detected. ABs were engulfed by monocyte-derived phagocytes. These findings suggest that immunogenic molecules are actively translocated into ABs followed by a rapid engulfment of the latter by environmental phagocytes. In autoimmune diseases, a defect in the clearance of ABs or AB formation may contribute to the development of autoimmunity.